Impact of donor and recipient Epstein-Barr Virus serostatus on outcomes of allogeneic hematopoietic cell transplantation: a systematic review and meta-analysis - Kołodziejczak, Michalina (Ann Hematol, 2021)
Allogeneic hematopoietic cell transplant (allo-HCT) is a potentially curative therapeutic strategy that showed encouraging long-term outcomes in hematological diseases. A number of factors can influence post-transplant clinical outcomes. While Epstein-Barr virus (EBV) constitutes a trigger for development of various adverse conditions, no clinical study yet has been powered to assess the effect of EBV serostatus on the clinical outcomes in allo-HCT population. To systematically summarize and analyze the impact of donor and recipient EBV serostatus on transplant outcomes in allo-HCT recipients, meta-analyses were conducted. Selected endpoints were overall survival (OS), relapse-free survival (RFS), relapse incidence (RI), non-relapse mortality (NRM), acute graft-versus-host disease (aGVHD), chronic graft-versus-host disease (cGVHD), and de novo cGVHD. Three studies with 26,650 patients, transplanted for acute leukemias, lymphomas, chronic hematological malignancies, or non-malignant hematological diseases were included in the meta-analysis. In the whole population, with a total of 53,300 donors and recipients, the rate of EBV seropositivity was 85.1%, including 86.6% and 83.6% among transplant recipients and healthy donors, respectively. Donor EBV seropositivity increased the risk of cGVHD by 17%, de novo cGVHD by 14%, and aGHVD by 5%. Recipient EBV seropositivity increased the risk of cGVHD by 12%, de novo cGVHD by 17%; increased NRM by 11%, increased RI by 11%, decreased OS by 14%, and decreased RFS by 11%. In performed meta-analyses, donor and recipient EBV seropositivity was found to have a significant impact on transplant outcomes in patients after allo-HCT.